Generalized pustular psoriasis (von Zumbusch) - Romiti,Ricardo (2022)
Abstract Generalized pustular psoriasis (von Zumbusch) is a rare and acute eruption characterized by multiple sterile pustules over an erythematous and edematous background, eventually associated with psoriasis vulgaris. Classically, it manifests as a potentially severe systemic picture and demands prompt diagnosis and intervention. The duration of each flare-up and intervals between the pustular episodes is extremely variable. Recently, genetic abnormalities have been identified mainly in the familial and early variants of this disease. The therapeutic arsenal is limited; however, new drugs being evaluated aim to control both pustular flare-ups and disease recurrences.